ASSISTANCE IN THE DISTRIBUTION OF ZAKAT FUND MANAGEMENT AT BAZNAS MEDAN CITY - Fadhillah Irwani Saragih (Cahaya Ilmu Bangsa, 2024)
This community service activity program aims to assist BAZNAS Medan City in managing and distributing zakat funds through the Medan Cares Program. The method used in this community service activity is assistance in distribution and field surveys regarding people who apply for assistance from BAZNAS. The implementation of assistance at BASNAS City of Medan has the main focus on assisting the management and distribution of zakat funds. Based on the community service activities carried out, it shows that with management and distribution assistance in accordance with Islamic law, zakat funds are more productive and their distribution is right on target, especially for mustahiq who are around the BAZNAS area of Medan City. The distribution and management of zakat funds at BAZNAS in Medan City have been carried out properly and effectively, as can be seen from the distribution of food packages every month for the poor and financial assistance for the renovation of residents' houses that are no longer livable, even in supporting the distribution of funds so that BAZNAS does not misuse supervision efforts for recipients of zakat funds, both direct and indirect supervision.